(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2021)
The Tiscapa lagoon is a water resource located in the city of Managua. Recent studies Scientists showed that this body of water maintains very low oxygen levels, including less than 5%, the minimum record for finding aquatic life. The main reason for this phenomenon is that the matter that falls from the channels is deposited at the bottom of the lagoon and takes time to decompose, later the decomposing substances produce excess minerals that allow the proliferation of algae. Algae bloom reduces the amount of oxygen in any body of water, until it produces anoxia, which is why dozens of turtles and fish die in this lagoon. This impact environmental is anthropic, the inhabitants of the city of Managua have not known how to handle the materials that discard and reach the natural channels of water currents that have always flowed in the lagoon, the difference is that before the currents were natural and only had elements typical of sedimentation, but now these waters carry substances that are harmful to this natural resource that must be saved.